PENCEGAHAN RESIKO KEHAMILAN PADA CALON PENGANTIN DENGAN PENDIDIKAN KESEHATAN MELALUI MEDIA BOOKLET (Universitas Kadiri, 2022)
Brides-to-be are the right targets in an effort to improve the health of the period before pregnancy. Brides-to-be need to prepare reproductive health both in the bride and in the bride-to-be, so that after marriage can have a good health status in order to produce a quality generation. This service aims to increase knowledge, awareness, willingness and ability of the bride and groom to prevent the risk of pregnancy. The method used is to provide counseling to 10 respondents while keeping their distance. Counseling is delivered with the theme of preventing the risk of pregnancy in brides-to-be with health education through booklet media. The results of the counseling showed a significant increase in public understanding of the problem from 48.15% to 87.35%. Based on these results, it is hoped that the public can apply this knowledge correctly in order to realize the highest degree of public health